Characterization of undoped and Si‐doped bulk GaN fabricated by hydride vapor phase epitaxy. Issue 3 (10th March 2014) - Wang, Baozhu; Yu, Pingping; Kucukgok, Bahadir; Melton, Andrew G.; Lu, Na; Ferguson, Ian T.
Abstract: In this study, the optical, structural, electrical and thermoelectric properties of undoped and Si‐doped bulk GaN samples are investigated. The room temperature PL near band emission peaks of undoped and Si‐doped bulk GaN samples are 3.414 eV and 3.402 eV. The undoped and Si‐doped bulk GaN samples' PL spectra have different defect emission bands which are green band and red band with the maximum at 2.4 eV and 2.0 eV, respectively. At low temperature, the PL spectrum of undoped bulk GaN has well‐defined excitonic emission lines, A 0 X, D 0 X, FXA (n = 1, 2), while the PL spectrum of Si‐doped bulk GaN has just broad emission peaks at the similar energy level. The low temperature PL spectra of both undoped and Si‐doped samples clearly show the first, second and third longitudinal‐optical phonon (1 LO, 2 LO and 3 LO) replicas. There are no donor‐acceptor pairs and electron‐acceptors' emission in the PL spectra of the samples. The temperature dependence PL spectra of undoped GaN samples shows that the intensity ratio of the FXA to D 0 X decreases with the increase of the temperature. The full width at half maximum (FWHM) of D 0 X emission is about 4.7 meV. The carrier density of the undoped and Si‐doped bulk GaN are 4.58 × 10 15 and 2.41 × 10 18 cm –‐3, and the mobility of the undoped and Si‐doped bulk GaN are 1050 and 286 cm 2 V –1 s –1 . The FWHM of (0002) X‐ray diffraction rocking curve are 54 arcsec and 95 arcsec for the undoped and Si‐doped bulk GaN samples. The power factors of the undoped GaN sample and the Si‐doped GaN sample are 0.315 × 10 –4 W/mK 2 and 0.35495 × 10 –4 W/mK 2, respectively. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)